KONSEPTUALISASI FUNGSI-FUNGSI MANAJEMEN PENDIDIKAN PROFETIK DALAM AL QUR’AN; KAJIAN AYAT-AYAT KISAH NABI SULAIMAN AS - Razak, Abdul; Tanzeh, Ahmad (re-JIEM (Research Journal of Islamic Education Management), 2024)
This research aims to conceptualize the functions of prophetic educational management as contained in the Qur'an, particularly through the study of verses that narrate the story of Prophet Solomon (AS). Utilizing the content analysis research method, this study identifies and elaborates on the educational management principles applied by Prophet Solomon (AS), which include planning, organizing, implementing, and monitoring functions. In terms of planning, Prophet Solomon (AS) is known for his ability to formulate clear strategies and goals. Organizing is evident from his ability to structure his government and distribute tasks effectively. The implementation function is reflected in his ability to make decisions and implement policies wisely. Meanwhile, monitoring is conducted through strict control and evaluation mechanisms to ensure that tasks are executed according to plan. The findings indicate that the story of Prophet Solomon (AS) in the Qur'an provides practical and philosophical guidance relevant to the development of modern educational management. This study is expected to contribute theoretically to the field of Islamic education and offer a new perspective for education practitioners in implementing prophetic values in their educational management.